The inoculum effect and band‐pass bacterial response to periodic antibiotic treatment - Cheemeng Tan; Robert Phillip Smith; Jaydeep K Srimani; Katherine A Riccione; Sameer Prasada; Meta Kuehn; Lingchong You (Molecular Systems Biology)
Abstract The inoculum effect (IE) refers to the decreasing efficacy of an antibiotic with increasing bacterial density. It represents a unique strategy of antibiotic tolerance and it can complicate design of effective antibiotic treatment of bacterial infections. To gain insight into this phenomenon, we have analyzed responses of a lab strain of Escherichia coli to antibiotics that target the ribosome. We show that the IE can be explained by bistable inhibition of bacterial growth. A critical requirement for this bistability is sufficiently fast degradation of ribosomes, which can result from antibiotic‐induced heat‐shock response. Furthermore, antibiotics that elicit the IE can lead to ‘band‐pass’ response of bacterial growth to periodic antibiotic treatment: the treatment efficacy drastically diminishes at intermediate frequencies of treatment. Our proposed mechanism for the IE may be generally applicable to other bacterial species treated with antibiotics targeting the ribosomes.